Antioxidant properties of spice extracts - Wahyu Widowati; Hana Ratnawati; Winsa Husin; Maesaroh Maesaroh (Biomedical Engineering, 2014)
Objective : This study was conducted to determine the antioxidant activities of spice extracts including clove (Syzygum aromaticum L.), Indonesian cassia (Cinnamomum burmanni (C. Nees& T. Ness)), coriander (Coriandrum sativum L), nutmeg (Myristica fragrans Houtt), java cardamom (Amomum compactum Soland. Ex maton). Methods : This research was to evaluate antioxidant activities including 1,1-diphenyl-2picryl-hydrazyl (DPPH) scavenging activity, the value of superoxide dismutase (SOD), and total phenolic content. Results : The highest DPPH activity is clove and Indonesian cassia extracts with IC value 4.16 μg/ml and 5.46 μg/ml respectively. The highest SOD value are Indonesian cassia extract (9.1432 U/ml) at 500 µg/ml, 7.0045 U/ml at 125 µg/ml and 4.6751 U/ml at 31,25 µg/ml. Clove extract was the highest of phenolic content (188.35 µg/mg eugenol equivalent). Conclusion : Indonesian cassia extract have high antioxidant activities. Clove extract contain the highest eugenol compared with Indonesian cassia, coriander, nutmeg and java cardamom. Key Words: antioxidant; free radicals; spice; total phenolic content